Study habits and peer pressure as determinants of senior school performance in Biology - Oluyemi Akinleye Ogundiwin; Gabriel Segun Adewumi; Olubukola Joyce Olumide; Ayodele Gabriel Fasanya (Inovasi Kurikulum, 2025)
The research examined the influence of study habits and peer pressure on students’ academic performance in Biology in Egbeda Local Government Area, Ibadan, Oyo State, Nigeria. The research was motivated by the consistent decline in students’ achievement in Biology, a core science subject essential for scientific literacy and future careers. The study employed a correlational research design with a sample of 185 Senior Secondary II (SSII) Biology students. Three instruments were utilized: the Biology Study Habits Questionnaire (BSHQ) with 30 items, the Biology Peer Pressure Questionnaire (BPPQ) with 25 items, and the Biology Performance Test (BPT) with 20 items. Based on Spearman-Brown estimates, the reliability coefficients were 0.92, 0.82, and 0.80, respectively. Data were analyzed using multiple regression analysis. The results revealed that both study habits and peer pressure significantly correlated with students’ academic performance and served as significant predictors of learning outcomes. These findings highlight the critical role of psychosocial factors, such as study habits and peer pressure, in shaping students’ academic performance in Biology and provide a foundation for developing more adaptive teaching strategies and curricula responsive to adolescent learning needs.   Abstrak Penelitian ini mengkaji pengaruh kebiasaan belajar dan tekanan teman sebaya sebagai determinan terhadap prestasi akademik siswa dalam mata pelajaran Biologi di wilayah Egbeda, Ibadan, Negara Bagian Oyo, Nigeria. Latar belakang penelitian ini adalah rendahnya pencapaian akademik siswa dalam mata pelajaran Biologi, yang merupakan mata pelajaran sains inti dan berperan penting dalam literasi ilmiah serta pengembangan karier. Penelitian ini menggunakan desain korelasional dengan melibatkan 185 siswa kelas XI (SSII) sebagai sampel. Tiga instrumen digunakan, yaitu Biology Study Habits Questionnaire (BSHQ) sebanyak 30 butir, Biology Peer Pressure Questionnaire (BPPQ) sebanyak 25 butir, dan Biology Performance Test (BPT) sebanyak 20 butir. Koefisien reliabilitas masing-masing instrumen adalah 0,92, 0,82, dan 0,80 yang dihitung dengan rumus Spearman-Brown. Analisis data dilakukan menggunakan teknik regresi berganda. Hasil penelitian menunjukkan bahwa kebiasaan belajar dan tekanan teman sebaya berhubungan secara signifikan dengan prestasi akademik siswa dalam Biologi dan menjadi prediktor penting terhadap pencapaian belajar. Temuan ini menegaskan pentingnya faktor psikososial seperti kebiasaan belajar dan tekanan teman sebaya dalam memengaruhi hasil belajar biologi siswa, serta memberikan dasar bagi pengembangan strategi pembelajaran dan kurikulum yang lebih adaptif terhadap kebutuhan remaja. Kata Kunci: hasil belajar biologi; kebiasaan belajar; lingkungan belajar; tekanan teman sebaya